2021
DOI: 10.21203/rs.3.rs-46018/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vagus nerve stimulation ameliorates L-NAME-induced preeclampsia-like symptoms in rats through inhibition of the inflammatory response

Abstract: Background Preeclampsia is characterized by an excessive inflammatory response. Recent studies have shown that vagus nerve stimulation (VNS) has anti-inflammatory properties in vivo. This study aims to investigate whether VNS is safe for use during pregnancy and to explore the therapeutic potential and underlying mechanisms of VNS in PE. Methods Pregnant Sprague-Dawley rats were randomly chosen to receive N-nitro-L-arginine methyl ester (L-NAME)-containing water (preeclampsia-like mouse model) or saline (norma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…In this study, L-NAME was used to create a PE rat model, and elevated blood pressure and poor pregnancy were observed in rats, consistent with the results of several previous studies. 4749 However, it was also found that APOA1-AS siRNA significantly ameliorated the L-NAME-induced increases in SBP and DBP in PE rats, suggesting that APOA1-AS downregulation could play a role in lowering blood pressure. In addition, APOA1-AS siRNA also reduced the expression levels of E-cadherin, ICAM-1 and VCAM-1 in placental tissues of PE rats, which further verified the in vitro experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, L-NAME was used to create a PE rat model, and elevated blood pressure and poor pregnancy were observed in rats, consistent with the results of several previous studies. 4749 However, it was also found that APOA1-AS siRNA significantly ameliorated the L-NAME-induced increases in SBP and DBP in PE rats, suggesting that APOA1-AS downregulation could play a role in lowering blood pressure. In addition, APOA1-AS siRNA also reduced the expression levels of E-cadherin, ICAM-1 and VCAM-1 in placental tissues of PE rats, which further verified the in vitro experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, through the activation of α7nAChR and the cholinergic anti-inflammatory pathway (CAP), the VNS inflammatory reflex is considered as a main neural control mechanism to prevent the production of proinflammatory mediators from innate immune cells (Borovikova et al, 2000). In a previous study, we reported that treatment with VNS significantly improved adverse pregnancy outcomes through anti-inflammatory pathway in L-NAME -induced PE model rats (Zheng et al, 2021). However, the clinical application of VNS is limited by its invasiveness.…”
Section: Introductionmentioning
confidence: 99%